Late Wisconsinan and Holocene development of Grand Lake Meadows area and southern reaches of the Saint John River Valley, New Brunswick, Canada - Broster, Bruce E.; Dickinson, Pamela J. (Atlantic Geoscience, 2015)
A 67 m near-continuous stratigraphic core was recovered from drilling at Grand Lake Meadows, located near the junction of Grand Lake and the Saint John River, approximately 40 km south of Fredericton, New Brunswick. From analyses of recovered samples and finite radiocarbon dating, four phases of development of the study site and surrounding environs were identified to have occurred following the Late Wisconsinan glacial maximum. Phase I, related to the formation of the DeGeer Sea, commenced more than 15 000 calyBP from deglaciation accompanied by marine transgression. Phase II began ~14 000 calyBP and continued until approximately ~8000 calyBP during which time there was major isostatic readjustment in the region and formation of a stratified, mostly brackish, ancestral Grand Lake and transformation into a mostly freshwater, Lake Acadia. Phase III began shortly after 8000 calyBP and continued until after 3000 calyBP accompanied by return of the Saint John River to a fluvialdominated system after down-cutting an outlet at the Reversing Falls gorge, and draining much of Lake Acadia. During phase IV, ~3000 calyBP to present, estuarine conditions were initiated as marine water advanced upstream over the Reversing Falls, leading to the development of the modern river system and Grand Lake Meadows.